Unlikely friendships : 47 remarkable stories from the animal kingdom - Holland, Jennifer S. (Workman Pub., 2011)
Presents a collection of stories about animals who have forged unlikely, abiding bonds with other animals of different species, from Koko the gorilla and All Ball the kitten to Owen the hippo and the tortoise Mzee.